Efektivitas Pengembangan Strategi Promotion Mix dalam Produk Tabungan Mudharabah Muthalaqah - Mairanda .; Purnama Putra (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2015)
This study aims at finding out the effectiveness of promotion mix strategy to introduce a saving product with the intention of ‘mudharabah muthiaqah’ at BNI Syatiah of Bekasi branch. In this study, the problems are identified as: first, how effective the promotion mix strategy is to be used to introduce a saving product with the intention of ‘mudharabah muthiaqab' and second: what kind of promotion mix method is the most effective to introduce a saving product with the intention of 'mudharabah muthiaqah at BNI Syatiah of Bekasi branch. The study employed mixed method or a combination between qualitative and quantitative approaches using concurrent embedded method. The study aims at describing the concept and mechanism of doing the most effective promotional strategy applied by BNI Syatiah of Bekasi branch in the year of2011-2012. For the qualitative approach, the instrument used was the writer himself, while the qualitative data was gained from questionnaires. The research result shows that the use of promotion mix strategy to to introduce a saving product with the intention of ‘mudharabah muthiaqah ’ at BNI Syariab of Bekasi branch was effective with the increase of account number of48.64% in 2012. However, the most effective promotion was “word of mouth" with the indication of80% gained Jwm the questionnaires